What do home videos tell us about early motor and socio-communicative behaviours in children with autistic features during the second year of life: an exploratory study - Zappella, Michele; Bölte, Sven (Early human development, 2015)
Background: Little is known about the first half year of life of individuals later diagnosed with autism spectrum disorders (ASD). There is even a complete lack of observations on the first 6months of life of individuals with transient autistic behaviours who improved in their socio-communicative functions in the pre-school age. Aim: To compare early development of individuals with transient autistic behaviours and those later diagnosed with ASD. Study design: Exploratory study; retrospective home video analysis. Subjects: 18 males, videoed between birth and the age of 6months (ten individuals later diagnosed with ASD; eight individuals who lost their autistic behaviours after the age of 3 and achieved age-adequate communicative abilities, albeit often accompanied by tics and attention deficit). Method: The detailed video analysis focused on general movements (GMs), the concurrent motor repertoire, eye contact, responsive smiling, and pre-speech vocalisations. Results: Abnormal GMs were observed more frequently in infants later diagnosed with ASD, whereas all but one infant with transient autistic behaviours had normal GMs (p<0.05). Eye contact and responsive smiling were inconspicuous for all individuals. Cooing was not observable in six individuals across both groups. Conclusions: GMs might be one of the markers which could assist the earlier identification of ASD. We recommend implementing the GM assessment in prospective studies on ASD.
Gesehen am 20.12.2018
Available online 31 July 2015